A size-dependent viscoelastic normal contact model for particle collision. (August 2017) - Ye, Yang; Zeng, Yawu
Highlights: A viscoelastic normal contact model is proposed to calculate particle collision. The model alleviates the influence of unphysical tension force on calculated results. The NRC of marble spheres has strong size effect and velocity effect. The model can more accurately describe experimental results than other models. The model can predict the NRC of smaller or larger particles. Abstract: Considering different energy dissipation mechanisms, many normal contact models have been proposed. However, the size effect and velocity effect of normal restitution coefficient (NRC) cannot always be accurately described. In addition, most of the normal contact models have unphysical tension stage for particles without adhesion during the simulation of particle collisions. Such problems limit the application of discrete element method (DEM) in particle dynamics. Given such limitations, the normal contact model proposed in the present work consists of a nonlinear Hertz spring and a size-dependent nonlinear dashpot, and the model parameters are determined by the NRC obtained in lab tests. Compared with other viscoelastic contact models, the current model can effectively alleviate the influence of unphysical tension force stage on the calculated results, satisfying the accuracy requirement of calculation, and accurately describe the size effect and velocity effect of the NRC of marble spheres at the same time. Besides, due to the viscous force, the contact time calculated by the current model is a little larger than the elastic contact time. The relationship between model parameters and particle size has been analyzed, which shows the law of K 1 conforms to exponential decay law and the K 2 conforms to hyperbolic tangent function. Graphical abstract: A size-dependent viscoelastic normal contact model is proposed to simulate particle collision. The figure shows that the current model can accurately describe the size effect and velocity effect of the normal restitution coefficient of marble spheres.